1998
DOI: 10.1002/pro.5560070321
|View full text |Cite
|
Sign up to set email alerts
|

Motional dynamics of residues in a β‐hairpin peptide measured by 13C‐NMR relaxation

Abstract: Structurally characterizing partially folded peptides is problematic given the nature of their transient conformational states. I3C-NMR relaxation data can provide information on the geometry of bond rotations, motional restrictions, and correlated bond rotations of the backbone and side chains and, therefore, is one approach that is useful to assess the presence of folded structure within a conformational ensemble. A peptide 12mer, RIGITVNG7KTYGRI2, has been shown to partially fold in a relatively stable /3-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…(referred to as E ROT in that paper 12 ) for either methyl group of 2.2 kcal/mol. In GVG, E j values for valine methyl group rotations are considerably larger (4.7 kcal/ mol for C ␥1 and 3.4 kcal/mol for C ␥2 ), suggesting increased side-chain/ backbone and/or side-chain/solvent interactions for valine methyls in this tripeptide.…”
Section: Figurementioning
confidence: 98%
See 3 more Smart Citations
“…(referred to as E ROT in that paper 12 ) for either methyl group of 2.2 kcal/mol. In GVG, E j values for valine methyl group rotations are considerably larger (4.7 kcal/ mol for C ␥1 and 3.4 kcal/mol for C ␥2 ), suggesting increased side-chain/ backbone and/or side-chain/solvent interactions for valine methyls in this tripeptide.…”
Section: Figurementioning
confidence: 98%
“…Since one methyl group is always closer to the carbonyl oxygen of the backbone, this energetic difference most probably results from interactions of these methyl groups with backbone atoms. 12 In a partially folded, ␤-hairpin peptide, 12 valine (V5) methyl i values at 303 K are equal to 28 ps for C ␥1 and 23 ps for C ␥2 with a rotational activation energy E j a Correlation times CH , for motions of methyl group CH bonds given in picoseconds. Activation energies E CH , for these motions are given in kcal/mol.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Using molecular dynamics simulations on model peptides in a-helix and b-sheet structures, it was observed that the magnitude and sign of c fc are dependent upon f, c angles within a structural element: in an a-helix, c fc is negative and in a b-sheet, c fc is positive. As initial verification of the model, c fc was found to be positive in two partially-folded b-sheet0hairpin-forming peptides, indicating that C a H internal motions primarily occur along the sheet as "twisting" type motions~Daragan et al Ramirez-Alvarado et al, 1998!. In the present study, 13 C and 15 N NMR relaxation experiments were performed on the hydrophobic staple-helix peptide in water and in water0TFE solution from 5 to 30 8C. Five hydrophobic residues, F2, A5, L7, A8, and A10, were uniformly 13 C0 15 Nenriched, and proton-coupled and -decoupled NMR relaxation measurements were acquired at four Larmor frequencies~62.5, 125, 150, and 200 MHz for 13 C!.…”
mentioning
confidence: 99%